Patient Blood Management in Pediatric Cardiac Surgery: A Review. (October 2018) - Cholette, Jill M.; Faraoni, David; Goobie, Susan M.; Ferraris, Victor; Hassan, Nabil
Abstract : Efforts to reduce blood product transfusions and adopt blood conservation strategies for infants and children undergoing cardiac surgical procedures are ongoing. Children typically receive red blood cell and coagulant blood products perioperatively for many reasons, including developmental alterations of their hemostatic system, and hemodilution and hypothermia with cardiopulmonary bypass that incites inflammation and coagulopathy and requires systemic anticoagulation. The complexity of their surgical procedures, complex cardiopulmonary interactions, and risk for inadequate oxygen delivery and postoperative bleeding further contribute to blood product utilization in this vulnerable population. Despite these challenges, safe conservative blood management practices spanning the pre-, intra-, and postoperative periods are being developed and are associated with reduced blood product transfusions. This review summarizes the available evidence regarding anemia management and blood transfusion practices in the perioperative care of these critically ill children. The evidence suggests that adoption of a comprehensive blood management approach decreases blood transfusions, but the impact on clinical outcomes is less well studied and represents an area that deserves further investigation.